A Survey on Multi-Layer Mimo for Lte/Lte-Advanced - Devi.J, Anjana; R. Dhaya, Dr; R. Kanthavel, Dr (International Journal of Engineering and Technology, 2018)
The primary intention of the paper is to explore on various Multi-Layer MIMO approaches for the higher system performance. MIMO technique is said to be the key technology in LTE-A to achieve the spatial diversity in the system. Multi-Layer MIMO is the enhancement to the MIMO technology where multiple streams of data could be transferred to different layers for optimization with increased capacity in the network in high SNR condition. In a massive MIMO system, the cell interference hinders the system performance due to high channel dimensionality. The main design objective of the Multi-Layer MIMO techniques studied is to reduce the Cell Interference with lower complexity.Â Â